Increasing the effectiveness of educational technologies in the foreign languages learning process by linguistic students (comparative analysis of Russian, Indonesian and Egyptian experience) - Pradana, Mahir; Rintaningrum, Ratna; Kosov, Mikhail; Bloshenko, Tatiana; Rogova, Tatyana; Singer, Nermeen (Frontiers in Education, 2022)
The aim of the study is to investigate the effectiveness of educational technologies in the foreign language learning process by linguistic students. The focus is to compare the experiences of Russia, Indonesia, and the Egyptian language experience regarding effective of educational technologies. The role of educational technologies has gained significant importance recently; therefore, considering this aspect, the study focused on a comprehensive discussion on this aspect using previous literature and argues what has been examined previously. The rationale and significance of the study are provided, along with the brief structure of the research. Besides, the study opts for a quantitative methodology to present empirical insights into the use of educational technologies in the foreign language learning process by linguistic students in Russia, Indonesia and Egypt. To analyze and interpret the research data, a descriptive technique is used where data was collected from 90 students (30 from each country). The collected data was analyzed using statistical tools, namely SPSS, where descriptive analysis was used to determine the effectiveness of educational technologies in the foreign language learning by Russian, Indonesian, and Egyptian students. The data findings revealed that the use of educational technologies in foreign language learning facilitated the learning process for the students with the integration of various technologies ranging from computer-assisted activities and audio-visual devices to online resources and social media. The findings also revealed that the utilization of technology-assisted tools proliferated the foreign language learning, making the language learning process highly engaging and interactive, while enabling the students to have better control and autonomy over their learning, wider resource accessibility, helping improve the pronunciation, and enabling to interact with native speakers. Hence, the study concluded that technology positively contributed to the language learning experience of the students, irrespective of the location.